KRITIK SOSIAL DALAM NOVEL PERSIDEN KARYA WISRAN HADI - Septiani, Wahyu Ririn (Pendidikan Bahasa Indonesia, 2014)
This study aims to (1) describe the forms of social criticism contained in the novel Persiden by Wisran Hadi, (2) describe the causes of the social criticism in the novel Persiden by Wisran Hadi. This study is a qualitative study using a descriptive method that exposes the facts found in the object of research. The data in this study in the form of words, sentences and dialogue related to social criticism. Sources of data in this study is novel Persiden by Wisran Hadi.Based on the research results of data obtained forms of social criticism that occurred in society in the novel Persiden by Wisran Hadi is a critique of the problems of poverty, family disorganization critique of the problems, criticism of the younger generation problem in modern society, a critique of the problems violation of norms society, a critique of environmental issues and criticism of bureaucratic problems. Some factors contributing to social criticism is economic, psychological, and cultural factors. Critics of the problem of poverty is to discuss indigenous issues centered on the material and the difference in the status of the rich and the poor. Critics of the family disorganisai discuss issues quarrel between families. Critics of the problems young people in modern society, it comes to the transition function of Surau, disagreement older and younger generations. Critics of the violation of the norms of society is to criticize the problems of prostitution. Environmental problems which criticized the environmental pollution problems. Critics of the problem is a matter of government bureaucracy that is not working properly.